Analisis Etika Bisnis Islam Terhadap Keberlangsungan UMKM di Kota Bima - Umifatun Suhadah; Husnatul Mahmudah; Muhammad Zia Ulhaq (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Micro, Small, and Medium Enterprises (MSMEs) make an important contribution to the economy of Bima City. However, the sustainability of this sector continues to face various challenges, particularly in the implementation of Islamic business ethics. This study aims to analyze the implementation of Islamic business ethics principles, particularly honesty, trustworthiness, and justice, among MSMEs in Bima City; identify supporting and inhibiting factors; and formulate strategies to strengthen their application. This study employs a descriptive qualitative approach involving 15 informants from various business sectors. Data were collected through in-depth interviews, observation, and documentation. The findings indicate that the implementation of the principles of honesty and justice remains varied. Some MSME actors still make ethical compromises due to price competition pressure and limited capital. In contrast, the principles of trustworthiness and responsibility tend to be applied more consistently, particularly among Tembe Nggoli woven-fabric artisans, who regard the preservation of traditional motifs as part of their cultural trust. The main supporting factors for the implementation of Islamic business ethics include the community’s high level of religious awareness and local government support. Meanwhile, the inhibiting factors include unhealthy price competition, low Islamic financial literacy, and weak monitoring mechanisms. The recommended strengthening strategies include improving halal literacy, expanding access to Islamic financing, developing a value-based business ecosystem, promoting ethical MSME digitalization, and establishing community-based participatory monitoring.